Law Enforcement against Perpetrators of Sexual Violence Crimes Committed by Children - Bawono, Bambang Tri; Saktiawan, Muhammad Dias (LifeSciFi, 2025)
The large number of cases of sexual violence that occur in the world, especially in Indonesia, is certainly an irony that must be resolved together. The reason is, the increasing number of sexual violence rimes hows that criminal law as a way to prevent and overcome crime is not running as it should. The type of research used in this study is sociological legal research whose data will later be analyzed using qualitative data analysis. Law enforcement efforts against perpetrators of crimes against children should be carried out more through the restorative justice or diversion method by prioritizing the child's future. The implementation of diversion against children as perpetrators of crimes, it is ecessary to explain the requirements for implementing diversion in the form of a threat of less than seven years. This is because the imposition of criminal sanctions for criminal acts cannot be separated from the minimum and maximum threats, so that the implementation of diversion which can only be carried out under seven years results in legal uncertainty.